Research on the upgrading of China’s regional industrial structure based on the perspective of green finance - Kong, Haojia; Xu, Yun; Zhang, Ruizhe; Tang, Decai; Boamah, Valentina; Wu, Guangliang; Zhou, Biao (Frontiers in Environmental Science, 2023)
Under the initiative of sustainable development, green financial mechanisms have become an important object to study environmental protection and reduce energy consumption and environmental pollution. This paper explores the mechanism of green finance’s effect on China’s industrial structure through panel regression and mediating effect models using panel data from 30 Chinese provinces and cities from 2009 to 2019. The findings show that 1) the level of green finance is high in both eastern and central regions, but the industrial structure in the eastern region is the most balanced and reasonable. From the results, the consistency between the industrial structure and the level of green finance development is stronger in eastern China. 2) The study of the mechanism of green finance’s role through the intermediary effect model shows that there is an overall mechanism of green finance influencing the upgrading of industrial structure through the financial sector in China, but it is manifested as partial intermediation, and the direct role of green finance on the industrial structure is more obvious. 3) In the analysis of regional heterogeneity, the intermediary role of the financial industry does not exist in the eastern and western regions, while the central region shows a masking effect. In response to these results and to promote the transformation and upgrading of industrial structure, the recommendation of this paper is to focus on the important role of financial institutions in developing green finance to adjust industrial structure, especially in the central region, where both green finance and industrial structure are at an intermediate level. Each region should adjust its industrial structure according to the time and place and promote upgrading the industrial structure.